In situ synchrotron radiation investigation of V2O5–Nb2O5 metastable compounds: transformational kinetics at high temperatures with a new structural solution for the orthorhombic V4Nb20O60 phase. Issue 48 (24th November 2020) - Caggiu, Laura; Iacomini, Antonio; Pistidda, Claudio; Farina, Valeria; Senes, Nina; Cao, Hujun; Gavini, Elisabetta; Mulas, Gabriele; Garroni, Sebastiano; Enzo, Stefano
Abstract : In situ synchrotron and conventional XRD patterns were solved for the phase developed at 700 °C with the Amm 2 orthorhombic space group, lattice parameters a = 21.187 Å; b = 3.827 Å; c = 19.377 Å; β = 119.83° and chemical composition V4 Nb20 O60 (ρ = 4.09 g cm −3 ). Abstract : Due to the considerable interest in vanadium niobium oxides as a lithium storage material, the kinetics and transformation processes of the V2 O5 –5Nb2 O5 system have been investigated by in situ synchrotron powder X-ray diffraction. The diffraction data after the thermal treatments selected with a view on the most significant features were supplemented with specific ex situ experiments conducted using a laboratory rotating anode X-ray diffractometer. The morphological changes of the mixed powders assuming an amorphous and nanocrystalline solid solution structure as a function of the temperature were inspected by scanning electron microscopy observations. The structural solution of the powder diffraction pattern of the phase recorded in situ at a temperature of about 700 °C was compatible with an orthorhombic crystal structure with the space group Amm 2. The obtained lattice parameters for this structure were a = 3.965 Å; b = 17.395 Å, c = 17.742 Å, and the cell composition was V4 Nb20 O60, Pearson symbol oA84, and density = 4.10 g cm −3 . In this structure, while the niobium atoms may be four-, five-, and six-fold coordinated by oxygen atoms, the vanadium atoms were six-fold or seven-fold coordinated. At the temperature of 800 °C and just above, the selected 1 : 2 and 1 : 3 V2 O5 –Nb2 O5 compositions, respectively, returned mostly a tetragonal VNb9 O25 phase, in line with earlier observations conducted for determination of the stability phase diagram of such quasi-binary systems.